Bending toward justice: the Birmingham church bombing that changed the course of civil rights - Jones, Doug (All Points Books, 2019)
Introduction: the arc of history -- The bombing -- Baxley -- Langford -- The job -- Rudolph -- Grand juries -- Sucker punched -- Blanton -- Politics & dementia -- Cherry -- Epiphanies 369 chapter twelve: honoring the children -- One more chance -- Connecting the dots.